LITERATUR REVIEW: PENGGUNAAN GAME ONLINE SEBAGAI STRATEGI KOPING DESTRUKTIF DI MASA PANDEMI COVID-19 - Azizah Heru, Maulidiyah Junnatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
As the internet age is growing rapidly, one of the benefits of the development of the internet is for entertainment facilities, for example to play online games. Online games are an audio and visual based game that is played over the internet network. Objective : To find out if the use of online games during the COVID-19 Pandemic is a destructive coping state. Methods : The source of the article used is through a database search google scholar, science direct and elsiver. Article searches are restricted from 2016 to 2021. The keywords used in the article searches are